2015
DOI: 10.1111/epi.12956
|View full text |Cite
|
Sign up to set email alerts
|

Emotional functioning: Long‐term outcomes after pediatric epilepsy surgery

Abstract: Summary Objective Children with epilepsy are at a high risk for developing symptoms of anxiety and depression. By improving seizure control, epilepsy surgery has the potential to improve patients’ anxiety and depression symptoms. Few studies have assessed the long‐term outcomes of anxiety and depressive symptoms after pediatric epilepsy surgery while using an appropriate control group. This study examined anxiety and depressive symptoms 4–11 years after surgery in surgical patients and in a control group of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
2
9
0
2
Order By: Relevance
“…However, there was lack of consensus with respect to changes in behavior and well-being after surgery amongst those who were seizure-free, with some reporting no change in behaviour 17,18 or well-being 18,19,21 and others reporting an improvement in behaviour 19,22 or wellbeing. 20,36,37 Potential reasons for the lack of consensus in findings could be related to small sample size, 17,23 use of variable HRQoL instruments, lack of a pharmacological comparison group, [17][18][19][20] or lack of presurgical baseline HRQoL measurements. [20][21][22][23] Figure 2: The relationship between treatment (surgery vs pharmacological management) and total Quality of Life in Childhood Epilepsy (QOLCE) score at 1-year follow-up is mediated by seizure control, adjusting for baseline total QOLCE score.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was lack of consensus with respect to changes in behavior and well-being after surgery amongst those who were seizure-free, with some reporting no change in behaviour 17,18 or well-being 18,19,21 and others reporting an improvement in behaviour 19,22 or wellbeing. 20,36,37 Potential reasons for the lack of consensus in findings could be related to small sample size, 17,23 use of variable HRQoL instruments, lack of a pharmacological comparison group, [17][18][19][20] or lack of presurgical baseline HRQoL measurements. [20][21][22][23] Figure 2: The relationship between treatment (surgery vs pharmacological management) and total Quality of Life in Childhood Epilepsy (QOLCE) score at 1-year follow-up is mediated by seizure control, adjusting for baseline total QOLCE score.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected as part of a larger study examining multiple long‐term outcomes following epilepsy surgery in childhood, including quality of life (Puka & Smith, ) and emotional functioning (Tavares, Puka & Smith, ). The study was approved by the Research Ethics Board of the Hospital for Sick Children, and informed consent/assent was obtained from the patients and/or their parents.…”
Section: Methodsmentioning
confidence: 99%
“…Cutoff scores on the scales allow for scores to be classified as “normal,” “borderline,” or “clinical”; those in the borderline and clinical range score at ≥93rd percentile. Due to small sample sizes of patients in the borderline and clinical range (ranging from 0 to 20 patients), scores falling in these latter classifications were categorized together as “abnormal.” As part of the larger research project, we have previously reported on a subset of other subscales of the ABCL in this sample and on intellectual outcomes …”
Section: Methodsmentioning
confidence: 99%
“…Due to small sample sizes of patients in the borderline and clinical range (ranging from 0 to 20 patients), scores falling in these latter classifications were categorized together as "abnormal." As part of the larger research project, [13][14][15] we have previously reported on a subset of other subscales of the ABCL in this sample 15 and on intellectual outcomes. 14 Patients were asked to complete a demographic questionnaire inquiring about their current education, employment, income, and social functioning.…”
Section: Study Measuresmentioning
confidence: 99%